2017
DOI: 10.1093/gji/ggx217
|View full text |Cite
|
Sign up to set email alerts
|

Between-event and between-station variability observed in the Fourier and response spectra domains: comparison with seismological models

Abstract: . (2017): Between-event and between-station variability observed in the Fourier and response spectra domains: comparison with seismological models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 44 publications
6
37
1
1
Order By: Relevance
“…The spectral ratios obtained for all earthquake pairs confirm that the relative difference of the between‐event residuals can be interpreted as changes in the earthquake frequency content of the ground motion records in the frequency band considered here (0.5–10 Hz). These results are consistent with recent tests conducted by Bindi et al () who have shown that the general trends observed in the Fourier domain (e.g., the between‐event dependence on stress drop) are also observed for the response spectra even if, as expected from their definition, response spectra are smoothing the frequency‐to‐frequency variability of ground motions, in particular, at frequencies larger than 10 Hz. The theoretical dependencies between Fourier and Response spectra have been analyzed in detail by Bora et al ().…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The spectral ratios obtained for all earthquake pairs confirm that the relative difference of the between‐event residuals can be interpreted as changes in the earthquake frequency content of the ground motion records in the frequency band considered here (0.5–10 Hz). These results are consistent with recent tests conducted by Bindi et al () who have shown that the general trends observed in the Fourier domain (e.g., the between‐event dependence on stress drop) are also observed for the response spectra even if, as expected from their definition, response spectra are smoothing the frequency‐to‐frequency variability of ground motions, in particular, at frequencies larger than 10 Hz. The theoretical dependencies between Fourier and Response spectra have been analyzed in detail by Bora et al ().…”
Section: Discussionsupporting
confidence: 92%
“…Under certain conditions taking into account the limitations of the response spectra compared to the Fourier spectra, GMPEs may be used for applications that go well beyond seismic hazard assessment. In particular, between‐event residuals, which have been shown to be correlated with the stress drops (Bindi et al, , ; Oth et al, ), can be spatially analyzed in order to identify variations of the frictional properties of large seismogenic faults (Piña‐Valdés et al, ). The findings presented in this work are consistent with the downdip segmentation of the frictional properties on subduction interface proposed by Lay et al () and also with the main features of the frictional segmentation model proposed for Miyagi area by Satriano et al ().…”
Section: Discussionmentioning
confidence: 99%
“…In our approach, we integrate known, crustal physical properties into source-to-site, path-specific ground motion models. This is similar in nature to approaches using physical parameters or constraints in ground motion models from source properties, such as stress drop (Ameri et al, 2017;Baltay et al, 2017;Bindi et al, 2017;Kotha et al, 2016;Oth et al, 2017), or incorporation of kappa as a site parameter (e.g., Laurendeau et al, 2013). We use a dense data set from Southern California of over 123,000 peak ground acceleration (PGA) values from earthquakes of magnitudes~1 < M < 4.5 and a region-specific GMPE to find pathspecific residuals or deviations away from an average ground-motion per recording (Sahakian et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…(1) was built for both the Fourier spectra and acceleration response spectra (SA). Although the SA does not depend linearly on the input motion, Bindi et al (2017) showed that the amplification functions obtained for SA (GIT_SA) are comparable to those obtained for FAS, only differing in the high frequency range and overall amplification levels. The advantage of providing the spectral amplification in terms of SA instead of FAS is that they can be used directly to multiply the reference spectrum on rock to obtain the corresponding sitespecific response spectrum.…”
Section: Methodologies and Productsmentioning
confidence: 73%